PENGARUH KETEPATAN SASARAN ANGGARAN, SISTEM PENGENDALIAN MANAJERIAL SEKTOR PUBLIK DAN SISTEM PELAPORAN PADA AKUNTABILITAS KINERJA - Paramitha, Ida Ayu Made Dwiki; ., Gayatri (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This study aims to determine the effect of the budget target accuracy , the system of public sector managerial control and reporting systems on performance accountability . Methods of data collection in this research is using survey method. Population in this study is the Head SKPD , Head of Sub Division of General and Planning , as well as Head of Sub Division of Finance and Accounting . Data collected through questionnaires . The analysis technique used is multiple linear regression . The results showed that the accuracy of the budget target positive and significant impact on performance accountability Tabanan regency SKPD . Public sector managerial control systems and a significant positive effect on performance accountability SKPD . The results also showed the reporting system and significant positive effect on performance accountability SKPD.
Keywords: target Accuracy of the Budget, Public Sector Managerial Control, Reporting, Accountability